La comunicación organizacional y la imagen corporativa de la cooperativa de ahorro y Crédito Educadores Primarios del Cotopaxi CACEC LTDA. - Tapia Peralvo, María de los Angeles (2020)
The saving and credit cooperative Primary Teachers of Cotopaxi “CACEC” has 54 years of institutional life, along this time has not achieved to place in financial market due to the ocassional and deficient advertising campaign. These organizations provide financial services and contribute to the development of the local and national productive system. However, the lack of communication, difussion and corporate imagen of the saving and Credit Cooperative Benefits have limited its expansion and growing. Therefore, the objective of this investigation is to determine the relation between the organizational communication and corporative imagen of “CACEC” cooperative. The methodology was based on the cuantitative approach, descriptive search because they permit the studio and analysis of data through statistics, its design is correlational and explicative because of stablishing the variables relation and investigating the problema causes o situations of the study object. The research population was defined by sampling, the information gathering was made by the poll technique and survey instrument, it was applied to the internal and external clients of institution, the information process was made by means of SPSS software to proceed with the tabulation anda analysis of results to know collaborators, clients and partners´ criteria about the relation between the organizational communication and corporate imagen. Finally, Chi – squared was used as a statistics measure to evaluate the null hypothesis which was refused. With these results there is a plan of means adapted to the organization needs; its main tool is the massive media as: television, radio, press, and social networks, they help to communicate and difuse the benefits of “CACEC” Cooperative, this is the reason to propose three strategies according to the stablished objectives, to carry out control and evaluation of media plan montly through account opening, new partners, number of operations and goal fulfillment.